Manajemen Risiko Rantai Pasok Telur Ayam Ras Dengan Menggunakan Metode House Of Risk (Hor) Dan Iso 31000 Di Kabupaten Pesawaran - Sekar Kinasih; Taufiq Immawan (Riviera Publishing, 2025)
This study aims to identify and mitigate risks in the purebred chicken egg supply chain in Pesawaran Regency, Lampung Province. The approach used is a combination of the ISO 31000 framework and the House of Risk (HoR) method. The research was conducted on independent breeders and purebred chicken egg distributors, by collecting data through interviews, observations, and questionnaires. Risk identification was carried out using the Content Validity Index (CVI) method, then analyzed using the House of Risk phase 1 to determine the cause of priority risk based on the Aggregate Risk Potential (ARP) value. The eight priority risk causes are determined through the Pareto principle, then classified by risk level. The next stage is risk mitigation using the House of Risk phase 2, by calculating the Effectiveness to Difficulty (ETD-k.) ratio of the proposed mitigation strategy. The results show that the highest priority mitigation strategy is to improve service and fast delivery and provide loyalty programs to repeat customers. This research is expected to be able to contribute to systematic risk management, and can be used as a reference in improving the efficiency and sustainability of the purebred chicken egg supply chain in Pesawaran Regency